Vlastní jména v prózách Cirila Kosmače při překladu ze slovinštiny do češtiny / Nazwy własne w prozie Cirila Kosmača w przekładzie z języka słoweńskiego na język czeski (tłum. Marta Buczek) - Šnytova, Jana (Przekłady Literatur Słowiańskich, 2015)
Proper names in the prose written by Ciril Kosmač with regard to their translation from Slovenian into Czech Kosmač’s best prosaic works Spring Day, Tantadruj and Ballade on a Trumpet and a Cloud contain a great number of proper names, in particular, real toponyms from the South‑West of Slovenia, anthroponyms used in the village environment in the 1st half of the 20th century, and nicknames. Based on the analysis of the original texts and Benhart’s translation, we state that, when translating proper names, the translator used mostly transcription (loanwords), less frequently substitution, mainly for hypocorisms, and literal translation for nicknames. This approach maintains, even emphasizes, the atmosphere and color of the Slovenian environment, however, it also deprives readers of the organic elements of the original works. Key words: proper names, translation, Ciril Kosmač, František Benhart, Slovenian literature